Cellulase Accelerates Short‐Term Decay of Thatch‐Mat. (1st May 2014) - Berndt, William L.; Gaussoin, Roch E.; Vargas, Joseph M.
Abstract : Thatch‐mat (TM) is comprised of various cell wall polymers, including cellulose. As cellulase (CEL) hydrolyses cellulose it may accelerate TM decay. Research sought to determine if CEL from Trichoderma reesei accelerates decay of TM from hybrid bermudagrass [ Cynodon dactylon (L.) Pers. var. dactylon × C.transvaalensis Burtt‐Davy]. Release of CO2 –C from TM in response to two levels of applied CEL and a control was measured daily over 15 d, plotting percent TM‐C remaining vs. time. Fitting a double exponential model of the form y = a 0 e − bx + c 0 e − dx to resulting curves yielded rate constants for fast‐pool C and slow‐pool C. After 3 d, total CO2 –C released from untreated TM was 2.95 g kg −1, leaving 96.8% C remaining. Treating with 10 and 20 g CEL kg −1 TM increased CO2 –C release to 4.30 and 5.84 g kg −1, leaving 95.6 and 93.6% C remaining. Differences in percent C remaining at 15 d were insignificant, averaging 92%. It appeared untreated TM had lost as much C as treated. Treating with 10 g CEL kg −1 decreased turnover time of fast‐pool from 3.2 to 1.3 d, and slow‐pool from 451 to 309 d. Increasing the rate to 20 g CEL kg −1 did not further reduce turnover time of fast‐pool, but increased slow‐pool turnover time to 1466 d. Results suggested constituents subject to CEL hydrolysis, which ≈7%, mineralized faster with CEL treatment, but were quickly exhausted slowing subsequent decay. Cellulase accelerated short‐term decay, but did not increase total TM mineralized over 15 d.